Accumulation of Technogenic and Natural Radionuclides in the Don Delta Sediments - Matishov Gennadiy; Ilyin Gennady; Polshin Vladimir; Usyagina Irina (Russian Journal of Earth Sciences)
The study of current sedimentation processes and radioactive contamination in the total area of the Don Delta is the research goal. The presented paper contains data analysis of radioecological and lithologic studies on bottom sediments, sampled in the northern part of the Don Delta in 2022. Based on the research results obtained, the authors provide the characteristics of the current conditions of sedimentation and specific activity of artificial and natural radionuclides in fluvial deposits, as well as indicate that similar in characteristics sandy-silty aleurites and sandy aleurite-clayish silts with inclusions of plant and shell detritus compose the bottom sediments of numerous braided channels. The authors determined the zonal accumulation character of both 137Cs technogenic and 226Ra, 40K, and 232Th natural radionuclides which conditions their accumulation and content increase from the lower delta to the upper delta areas. The velocity of currents in the braided channels (bayous) and related sedimentation conditions of suspended matter, as well as the lithotype of the bottom ground determine the indicated regularity. We assume that unlike 137Cs the distribution of natural radionuclides (40K, 226Ra, and 232Th) mainly depends on the mineral content of sediments entering the delta with the river runoff. Relatively low indices – on average ca. 9 Bq/kg of dry weight (d.w.) – characterise the current range of 137Cs radioisotope concentrations in the sediments of the Northern Don Delta. Such a level of specific activity is of no danger to the regional ecosystem.